PERENCANAAN EVALUATIF SISTEM PENGELOLAAN DATA CORPORATE CULTURE PURPOSE (CCP) BERDASARKAN KESESUAIAN LAPORAN PT PLN UID S2JB - Ratih Tarina Utami Putri; Aminullah Imal Alfresi (CV. Denasya Smart Publisher, 2025)
This research aims to evaluate the data management system of Corporate Culture Purpose (CCP) implemented at PT PLN (Persero) UID S2JB. Currently, the CCP data management process relies on a third-party application (TeamGantt), which has several limitations such as lack of integration with PLN’s internal systems, absence of automated validation, and inconsistency in reporting formats. The research method uses an evaluative approach with general and specific situation analysis, as well as problem identification to reveal the existing gaps. The results indicate that many reports do not comply with the established guidelines in terms of completeness, accuracy, and consistency. As a solution, this study proposes a more structured and integrated information system design for CCP data management to better support the company’s needs.